2023
DOI: 10.1021/acsami.3c02507
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Thermal Boundary Conductance across Wide and Ultrawide Bandgap Semiconductor Interfaces

Abstract: The emergence of wide and ultrawide bandgap semiconductors has revolutionized the advancement of next-generation power, radio frequency, and opto- electronics, paving the way for chargers, renewable energy inverters, 5G base stations, satellite communications, radars, and light-emitting diodes. However, the thermal boundary resistance at semiconductor interfaces accounts for a large portion of the near-junction thermal resistance, impeding heat dissipation and becoming a bottleneck in the devices’ development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 167 publications
2
5
0
Order By: Relevance
“…Converted to TBC, these values are less than 10 MW/m 2 ·K, greater than 100, and 10–100 MW/m 2 ·K. These ranges agree with the values reported in Tables and , as well as with values reported in existing literature . While deviations exist in the partially bonded regions, the inversions using sparse and dense measurement data show good agreement, suggesting an accurate inversion.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Converted to TBC, these values are less than 10 MW/m 2 ·K, greater than 100, and 10–100 MW/m 2 ·K. These ranges agree with the values reported in Tables and , as well as with values reported in existing literature . While deviations exist in the partially bonded regions, the inversions using sparse and dense measurement data show good agreement, suggesting an accurate inversion.…”
Section: Resultssupporting
confidence: 88%
“…Inferred thermal conductivity along the measurement line is shown in Figure 6a 1 and 2, as well as with values reported in existing literature. 43 While deviations exist in the partially bonded regions, the inversions using sparse and dense measurement data show good agreement, suggesting an accurate inversion.…”
Section: Inversion Of Line Measurement Datamentioning
confidence: 87%
“…A detailed description of the annealing technique can be found in ref. 57. In our simulations, we interestingly found that the amorphous structure preferentially converted into a rocksalt phase instead of the initialized wurtzite phase, as shown in Fig.…”
Section: Resultssupporting
confidence: 55%
“…To enhance heat dissipation, silicon carbide (SiC) has been utilized as a substrate due to its high thermal conductivity (∼350 W m –1 K –1 ) and relatively close lattice constant to GaN. However, the GaN/SiC interface typically exhibits limited thermal boundary conductance (TBC), , preventing the full utilization of the high thermal conductivity substrate . Consequently, numerous experimental and theoretical studies have been conducted to investigate and enhance thermal transport across GaN/SiC interfaces. …”
Section: Introductionmentioning
confidence: 99%